Perbandingan Efek Samping ARNI vs ACEi/ARB pada Terapi Gagal Jantung: Analisis - Anjar Nuryanto; Riana Suwarni (PT Kalbe Farma Tbk., 2025)
Introduction: Pharmacological treatment of heart failure continues to develop. Newer drugs such as ARNI (angiotensin receptor neprilysin inhibitor) have become standard for heart failure treatment. This systematic review aims to compare the side efects of ARNI with those of previous standard heart failure therapy. Methods: This research uses PRISMA rules to analyze articles from PubMed and Cochrane. Results: A total of 2,741 articles, excluding duplicates, were selected for title and abstract screening. Twelve articles met the requirements for thorough screening. Of the 12 articles, 4 articles were selected for systematic review analysis. There were 6,553 samples, 2,580 in the ARNI group and 2,390 in the ACEI/ARB group. ARNI was better in reducing the risk of decreased eGFR (RR: 0.51; 0.34-0.78) and the incidence of hyperkalemia (RR: 0.87; 0.76-0.99) but the risk of symptomatic hypotension was greater in the ARNI group (RR: 1.47; 1.23-1.70). Conclusion: The risk of hypotension as well as a reduced risk of cardiovascular death and rehospitalization was higher in the ARNI group, while the risk of decreased eGFR and hyperkalemia was higher in the ACEi/ARB group.